REPOSISI PERPUSTAKAAN PERGURUAN TINGGI SEBAGAI AGEN PERUBAHAN SOSIAL: PENYESUAIAN STRATEGIS DENGAN KERANGKA KAMPUS BERDAMPAK - Moch. Fikriansyah Wicaksono; Endry Putra; Rizki Fitria Dewi (Pustabiblia: Journal of Library and Information Science, 2026)
This article discusses the strategic repositioning of university libraries as agents of social change within the framework of the Impacted Campus policy. Libraries, which have been positioned as academic support units, need to be reformulated to become a major actor in community service, community empowerment, and knowledge-based social development. Using the literature review method, this article examines theories, policies, and practices both from Indonesia and abroad that demonstrate the real contribution of libraries in promoting community literacy, inclusive services, and knowledge co-production. The results of the study show that libraries have great potential in bridging the gap between academics and the social needs of the community. However, the realization of this concept faces a number of challenges, including an institutional structure that is not yet integrative, limited librarian capacity, and the absence of performance indicators that support the social function of libraries. The implications of these findings show that a systematic institutional strategy is needed to make libraries a strategic node in the implementation of the tridharma of higher education. This includes strengthening human resource capacity, developing cross-unit collaborative models, and supporting policies that are oriented towards social impact.